2013
DOI: 10.1103/physrevb.88.035433
|View full text |Cite
|
Sign up to set email alerts
|

Noise of a single-electron emitter

Abstract: I analyze the correlation function of currents generated by the periodically driven quantum capacitor emitting single electrons and holes into the chiral waveguide. I compare adiabatic and non-adiabatic, transient working regimes of a single-electron emitter and find the striking difference between the correlation functions in two regimes. Quite generally for the system driven with frequency Ω the correlation function depends on two frequencies, ω and Ω − ω, where is an integer. For the emitter driven non-adia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…We compare our formulas with the numerical results of a Floquet calculation properly modeling the emission process from a realistic periodic source . This emitter consists of the mesoscopic capacitor : a quantum dot with discrete levels connected through a QPC to the edge state that is driven by a gate applying a periodic square drive Vfalse(tfalse).…”
Section: Hong–ou–mandel Electron Collisions In the Integer Quantum Hamentioning
confidence: 99%
“…We compare our formulas with the numerical results of a Floquet calculation properly modeling the emission process from a realistic periodic source . This emitter consists of the mesoscopic capacitor : a quantum dot with discrete levels connected through a QPC to the edge state that is driven by a gate applying a periodic square drive Vfalse(tfalse).…”
Section: Hong–ou–mandel Electron Collisions In the Integer Quantum Hamentioning
confidence: 99%
“…These recent efforts have boosted the general interest in the study of noise [30] as a powerful tool to characterize the response of a conductor to a generic time-dependent driving potential [17,28,29,[31][32][33][34][35][36]. In particular, it has been shown that the noise carries information on the probability with which electron-hole pairs are created by the ac part of the driving [31,37,38] and it is sensitive to correlations between electrons and holes [39].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments of on-demand electron generation in electronic transmission channels have stimulated the theoretical study on the quantum-mechanical nature of the single electrons which are generated in the one-dimensional channel [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. * iyoda@noneq.c.u-tokyo.ac.jp…”
Section: Introductionmentioning
confidence: 99%